Fungsional Struktural Parson dalam Perubahan Sosial Desa Ponggok: Telaah Linimasa 2009 – 2023 - Iqmal Maulana Z; Zahran Fauzi H; Yilmaz Omar S; Ahsan Syamil R; Dede Sri Kartini (Pusat Riset dan Inovasi Nasional, 2025)
This study analyzes social change in Ponggok Village, Klaten, Central Java, from an impoverished village to a self-sufficient one, utilizing Talcott Parsons' structural functionalist framework and the AGIL model (Adaptation, Goal Attainment, Integration, Latency). Prior to 2006, Ponggok Village faced poverty, inadequate infrastructure, and limited employment opportunities, despite its significant potential for spring water. The transformation began in 2009-2013 with collaboration between the village head and academics for potential mapping and the establishment of the Village-Owned Enterprise (BUMDes) Tirta Mandiri. The period from 2014 to 2018 marked a